Formação do professor reflexivo/pesquisador em um curso de licenciatura em Química do Nordeste brasileiro : limites e possibilidades. - Lima, João Paulo Mendonça (2011)
The quality of teaching/learning of chemistry has been the subject of several discussions, having its favored comprehension by the need to better understand how the process is occurring in the initial formation of teachers of Chemistry. Formation of teachers has undergone several criticisms regarding the dissociation between theory and practice, the presence of a Technical rationality and formation models that approach a course with features of Baccalaureate. Thus, from the changes after the implementation of new Curriculum Guidelines for Graduation Courses (2002), we understand the contributions of increased and incorporation of disciplines and pedagogical practice along a degree course in Chemistry Graduation Course. This first analysis gave us some indication, but brings no guarantees about the understanding of the formation as it has the chemistry teacher. This way, we seek through interviews analyze the opinions of five formers about developed activities in the Graduation Course in Chemistry in Brazilian Northeast by conducting a case study. We analyze the proximity among course teachers and the teachers of the basic education, as well as their opinions about the characteristics and profile of the first class of graduates. This analysis was essential to achieve the main objective of the study, which was investigating the limits and possibilities of the formation of a teaching/learning teacher in Chemistry Graduation Course. The discussion of this work contributes to the understanding of various present problems in the process initial of Chemistry. The study shows that, though occurred advances in the structure of the curriculum in undergraduate chemistry and good prospects in improving the formation of undergraduates, the limitations made by the models of formation experienced by some teachers, our public politics, work implemented in isolation form, and short period of operation of the course are shown as limiting factors for a better quality of the proposal to form the reflective/researcher teacher, while we have identified some possibilities for teacher formation with the profile mainly due to concern about the quality of formation that is offered to undergraduates by former teachers of the course beyond the activities and attempt to overcome these problems in the course structure and the proper conception of the goals to be achieved during the initial formation process in the course graduation in Chemistry.